2015
DOI: 10.3109/13880209.2015.1043562
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress-related liver dysfunction by sodium arsenite: Alleviation byPistacia lentiscusoil

Abstract: Context: Pistacia lentiscus L. (Anacardiaceae) is an evergreen shrub widely distributed throughout the Mediterranean region. Pistacia lentiscus oil (PLo) was particularly known in North African traditional medicine. Thus, people of these regions have used it externally to treat sore throats, burns and wounds, as well as they employed it internally for respiratory allergies. PLo is rich in essential fatty acids, vitamin E and polyphenols. As a very active site of metabolism, liver is reported to be susceptible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 75 publications
2
12
0
Order By: Relevance
“…The significant reduction in RBC and Hb is probably due to the effect of the free radicals generated by nitrate on the red cells when certain free radicals, as O 2 .- and OH, are very reactive species able to cause membrane lipid damage. Moreover, in the presence of strong concentrations of these radicals, haemoglobin can easily oxidised 41 , 42 . Furthermore, PSO co-administration in rats' was found to keep the investigated parameters within their physiological ranges.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The significant reduction in RBC and Hb is probably due to the effect of the free radicals generated by nitrate on the red cells when certain free radicals, as O 2 .- and OH, are very reactive species able to cause membrane lipid damage. Moreover, in the presence of strong concentrations of these radicals, haemoglobin can easily oxidised 41 , 42 . Furthermore, PSO co-administration in rats' was found to keep the investigated parameters within their physiological ranges.…”
Section: Discussionmentioning
confidence: 99%
“…The latter is subsequently converted into nontoxic water and oxygen molecules by the action of CAT 48 . Nevertheless, GPx plays a pivotal role in H 2 O 2 catabolism and GST acts a key role in cellular detoxification 41 , 49 . It was found that small deviations in physiological concentrations may have dramatic effects on the resistance of cellular lipids, proteins and DNA to oxidative damage 49 .…”
Section: Discussionmentioning
confidence: 99%
“…5 Arsenic metabolism in the liver generates reactive oxygen species (ROS) which include dimethyl arsenic peroxyl ([(CH 3 ) 2 AsOO]) and dimethyl arsenic radical [(CH 3 ) 2 As]. [6][7][8][9] These reactions are catalysed by a cytosolic enzyme, methyltransferase, which uses S-adenosyl methionine (SAM, also known as S-adenosyl-L-methionine) as a methyl group donor. 10 The methylated arsenic intermediates can be more toxic than inorganic arsenate (As V ) or arsenite (As III ), which means under certain circumstances methylation activity can exacerbate arsenic toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Though the antioxidants were found to be useful, the mechanism was not clear. It is possible that the antioxidants (vitamin E and C) could play a role in reducing cellular oxidative stress produced by arsenic [24,25,26,27]. Vitamin A (Retinol) has the antikeratinizing effect and used as chemoprevention against some cancer particularly skin cancer [27,28].…”
Section: Discussionmentioning
confidence: 99%